Optimization of Bioethanol Production From Chlorella Vulgaris With Ca2+,Mg2+, and Zn2+ Ion Suplements Through Separated Hydrolysis and Fermentation Using Respon Surface Methodology - Muhammad Fakhrudin Zukhri; Afan Hamzah; Muhamad Khoirul Anam (IPTEK The Journal of Engineering, 2025)
Indonesia, with its wealth of natural resources, has the potential to develop bioethanol as an alternative to diminishing fossil energy sources. Third-generation bioethanol is a form of renewable energy and an environmentally friendly fuel derived from non-conventional biomass resources, particularly from microorganisms such as algae and cyanobacteria. This study focuses on optimizing the bioethanol production process from the microalga Chlorella vulgaris using the Separated Hydrolysis and Fermentation (SHF) method, with the addition of calcium ions (Ca^2+), magnesium ions (Mg^2+), and zinc ions (Zn^2+) to enhance bioethanol yield and concentration. The research procedure includes raw material pretreatment, acid hydrolysis, liquefaction, saccharification, fermentation, and distillation. The distillate samples are analyzed for bioethanol concentration using a refractometer and bioethanol density with a pycnometer. The effect of added medium components on the fermentation process is statistically analyzed using Analysis of Variance (ANOVA) in MINITAB Statistical Software and Response Surface Methodology (RSM) in DESIGN EXPERT 13. Statistical optimization of the fermentation process is performed using Central Composite Design (CCD). ANOVA analysis reveals significance with a P-Value < 0.0001 for bioethanol yield and concentration. Optimization results indicate an optimal yield of 17.087 percent with a concentration of 165.592 grams per liter, achieved with the addition of Ca^2+ at 164.755 parts per million, Mg^2+ at 146.279 parts per million, and Zn^2+ at 38.516 parts per million.